Interfacial capillary–gravity short-crested waves - Boughazi, Dalila; Debiane, Mohammed; Allalou, Nabil (Comptes Rendus. Mécanique)
This paper presents a method derived from Whitham’s variational formulation of the problem of interfacial capillary–gravity short-crested waves. It is developed for the resolution of the problem of waves generated by obliquely reflecting interfacial waves from a vertical wall. In essence, Whitham’s method is not changed, but computations are performed and arranged to produce a method that has been applied to a number of cases demonstrating the effectiveness and the flexibility of the approach. The performance of the method is illustrated in several examples including the case of harmonic resonance.